Les témoins muets mis en spectacle - Frédéric Chauvaud (Criminocorpus)
Objects, traces and clues are a more and more important. Better than the confession or testimony, they do not seem to be a personal appreciation. They are material things that no one can dispute. A knife, an axe, a gun are exhibits which are first presented to the public of the “cours d’assises”. The readers of the journal Detective turned into jurors. But the famous periodical does not merely to include objects. The photographs do not hesitate to show corpses, provoking fascination, horror and disgust.